Influencia de los recursos didácticos informáticos en el proceso de enseñanza-aprendizaje de los estudiantes del segundo año de bachillerato, especialidad administración de sistemas, del Colegio Fiscal Técnico Santa Rosa de la ciudad de Santa Rosa, provincia de El Oro, periodo lectivo 2012-2013. - Ramírez Cañar, Andrea Esthefanía (2012)
This research was conducted in order to find an appropriate methodology in the use of computer teaching resources in the teaching-learning process, as well as to know what level of knowledge of teachers and students about resources before mentioned.